CORRELATION BETWEEN SELF-EFFICACY AND INTEREST IN BECOMING A CHURCH COUNCIL MEMBER OF THE YOUTH AND STUDENT DEVELOPMENT COMMISSION AT GKJW JEMAAT SEMAMPIR - Akde Triyoga (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to examine the level of self-efficacy, the level of interest in becoming a church council member (Majelis Jemaat), and the relationship between self-efficacy and the interest in serving as a church council member at GKJW Jemaat Semampir. The background of this research is based on the low participation of youth in structural church ministries, particularly in the role of church council members. This study employs a quantitative approach with the Spearman correlation analysis technique. The results show that most respondents have a moderate level of self-efficacy (68.8%), while the remaining respondents fall into the high category (31.3%). The level of interest in becoming a church council member is equally distributed between the moderate and high categories, each at 50%. The Spearman correlation test resulted in a coefficient of 0.405 with a significant value of 0.022, indicating a positive and significant relationship between self-efficacy and the interest in serving as a church council member. The higher an individual's self-efficacy, the greater their interest in participating in structural church ministries. This finding supports Bandura’s theory, which states that self-efficacy influences a person’s motivation and involvement in an activity. Therefore, enhancing self-efficacy can be an effective strategy to encourage greater participation of youth in church leadership roles.